Lost Identity: the Disappearance of Cultural Identity - Molsawat, Taweesak (Asian Creative Architecture, Art and Design, 2012)
Abstract The focus of this paper will be on the influences of globalization on local community or vice versa regarding culture, and society particularly in design in Thailand. National economies are more open to one another than ever before. With international trade at an unprecedented level, much of what people consume is imported and much of what they produce is exported. Technologies, artistic moving, business practices, musical trends, and fads and fashions reach all corners of the developed world almost instantaneously. Global economy and culture form a nearly seamless web in which nation boundaries are increasingly irrelevant to trade, investment, finance and other social and cultural activities. There are no exceptions in Thailand. Thai culture has been affected by globalization through imitation of Western lifestyles. How this invasion of foreign cultures affects our culture and design approach. How can, we as a local, be able to withstand or keep our design identity with the influx of global movement. When the big companies in the world try to create design that satisfies or influences the global market, will this result in uninspired products that will characterize this broad global market? Or are we heading to other directions such as anti-globalization, anti-design, or post 09-11 era to encounter and create even more diverse design approaches to signify the subcultures or identity of the local creating the fabric web of communication and influence between local and global or vice versa. I believe that there will be more a variety of design approaches and niche markets to investigate in the future. We will see the crossed-over between cultures, life styles, art, and design between global and local. This will allow the flexibility for cross-cultural experiences, desires and needs. There will be a metamorphosis and mixture between local and global creating the hybridizations that allowed us to create a unique thought in order to find our own identity of design. Keyword: Global Community, Identity Crisis, Individual expression, Reproduction society